On the need and use of village hospitals in Ireland - Sigerson, George (Statistical and Social Inquiry Society of Ireland, 1882)
During an existence of some forty years the Irish Poor-law system has undergone some modifications for the better; and the test of time, whilst demonstrating beyond question the great benefits it has conferred upon the country has also shown that it may fitly receive further developments. The strain put upon it in times of exceptional distress brings conspicuously into view those hindrances to its perfect efficiency which in ordinary times escape the accustomed eye.
Read before the Society, 31 January 1882
Keywords: Village hospitals; Irish hospitals; Medical care; Rural hospitals; 314.15